From Conflct to the Post-Peace Agreement: Current Constitutional Affirs of the National Security Doctrine regarding Transitional Justice - Olano García, Hernán Alejandro (DIXI, 2016)
Purpose: this reflction article outlines the diffrent periods of violence in Colombia by presenting an analysis for post-conflct and reviewing some aspects of the national security doctrine to be applied in the context of demobilization and post-conflct according to transitional justice. Description: within the line of research into the history of institutions, the stages and causes of violence in Colombia are described since it has become a South American concern as bordering countries are affcted by the problems derived from the conflct itself. Point of view: while formulas of transition to peace have already been given by history, it is expressed that, from a legal perspective, the Treaty of Rome has not replaced the national ordinary criminal jurisdiction or the so-called transitional justice and that, as a fim step towards peace, agreements should include that investigations or trials are carried out in accordance with the national law and the fundamental constitutional rights protected by it. Conclusions: the new transitional justice may cause conflcts of power with High Courts since the new Peace Tribunal, with the presence of international judges, will be the new judicial closure body in Colombia.